Optimizing Da'wah From the Perspective of Da'wah Management: A Case Study of The ex-Samin Muallaf in Kudus, Central Java - Moh Rosyid (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2020)
This article based on research to description effort to be made preacher to Samin becomes muslim (mullaf) all this time not positioned object preacher. Usually Samin becomes muallaf because marriage by muslim. If not charged specially, Islam is not intact. Data of this article were collected through interviews, observations, documentations by Samin’s in Kudus, central Java by descriptive qualitative approuch. Way of preaching by techniques lecture (tablig), guidance (irsyad), managerial (tadbir), social development (tathwir). The muallaf (ex-samin context) tablig and guidance are it succesfully islamic enhancement. This is due islamic approuch and humanities between preacher (mubaligh) by muallaf/ex-Samin (mad’u). Which must be done again are tadbir and tathwir. Islamic organization, islamic figure, Indonesian Ulema Council (MUI), and Ministry of Religion Kudus through counseling must have an special agenda in order to be muallaf (ex-Samin) islamic understand step by step approuch by soft. All parties must work together for determine attidtude by a wise.Keywords: strategy, preacher, a wise, and sustainability.